The Costs of Related Diversification: The Impact of the Core Business on the Productivity of Related Segments - Kumar, M. V. Shyam (Organization Science, 2013)
I develop the thesis that in related diversified firms, the core business (in my analysis, the largest business) may provide benefits such as scope economies to a related segment, but it may also exert power and constrain the segment to act in its interests in various internal and external transactions. This enables the core business to shift productivity gains toward itself from the segment, which could lead to various inefficiencies within the related diversified firm. Using input/output flow data and a multilevel model with the segment as the unit of analysis, I first show that a segment’s productivity is lower compared with a single-business firm when it shares backward and forward complementarity (i.e., when it shares transactions with common suppliers and customers) with the core business. Correspondingly, I show that as a mirror image, the core business’s productivity is enhanced when the business shares backward and forward complementarity with segments and when segments are backward integrated with it (i.e., when the core business provides outputs to segments). These shifts in productivity and the attendant inefficiencies do not seem to be destroying the entire value from related diversification. Overall, the findings support the argument that the power and influence exerted by the core business—and concomitantly, the subsidization of the core business by related segments—is an important source of costs borne by segments in a related diversified firm.